2012
DOI: 10.1016/j.visres.2011.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal templates of transient attention revealed by classification images

Abstract: Visual attention is captured by transient signals in the periphery of the visual field, allowing enhanced perceptual representations in spatial tasks. However, it has been reported that the same cues impair performance in temporal tasks (e.g., Yeshurun, 2004; Yeshurun & Levy, 2003). This findings suggest that transient attention enhances the activity of slow, high-resolution channels, like parvocellular neurons, and/or shuts off faster channels better sensitive to low spatial frequencies, such as the ones of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 54 publications
3
10
1
Order By: Relevance
“…Whereas endogenous attention enhances or reduces resolution depending on the resolution constraints of the visual system, exogenous attention inflexibly enhances resolution. Our findings provide converging evidence for an automatic exogenous mechanism whose effects are invariant to the predictability of the cue (Giordano et al, 2009 ) and have been attributed to modulations of high-SF neurons that enhance spatial resolution and reduce temporal resolution (Carrasco et al, 2006 ; Megna, Rocchi, & Baldassi, 2012 ; Yeshurun & Levy, 2003 ; Yeshurun & Sabo, 2012 ). Our findings also provide further evidence for a more adaptive endogenous mechanism that improves both spatial and temporal discriminability (Barbot & Carrasco, 2017 ; Barbot, Landy, & Carrasco, 2012 ; Giordano et al, 2009 ; Hein, Rolke, & Ulrich, 2006 ; Yeshurun, Montagna et al, 2008 ).…”
Section: Discussionsupporting
confidence: 61%
“…Whereas endogenous attention enhances or reduces resolution depending on the resolution constraints of the visual system, exogenous attention inflexibly enhances resolution. Our findings provide converging evidence for an automatic exogenous mechanism whose effects are invariant to the predictability of the cue (Giordano et al, 2009 ) and have been attributed to modulations of high-SF neurons that enhance spatial resolution and reduce temporal resolution (Carrasco et al, 2006 ; Megna, Rocchi, & Baldassi, 2012 ; Yeshurun & Levy, 2003 ; Yeshurun & Sabo, 2012 ). Our findings also provide further evidence for a more adaptive endogenous mechanism that improves both spatial and temporal discriminability (Barbot & Carrasco, 2017 ; Barbot, Landy, & Carrasco, 2012 ; Giordano et al, 2009 ; Hein, Rolke, & Ulrich, 2006 ; Yeshurun, Montagna et al, 2008 ).…”
Section: Discussionsupporting
confidence: 61%
“…Earlier psychophysical work has ascribed related phenomena to attentional capture (Neri and Heeger, 2002;Megna et al, 2012). However, this interpretation is unlikely to account for the results reported here.…”
Section: Self-reinforcing Feedback Modelcontrasting
confidence: 64%
“…Experimental results show that the CPD is primarily due to the predominance of high-spatial frequencies at central locations, and that exogenous attention automatically enhances resolution by increasing sensitivity to higher spatial frequencies (Carrasco et al 2006b). Consistent with this finding, a classification image study showed that with exogenous attention, the perceptual templates become sharper and are characterized by stronger high-spatial frequency components (Megna et al 2012). In addition, both exogenous (Gobell and Carrasco 2005) and endogenous (Abrams et al 2010) attention increased perceived spatial frequency at the attended area.…”
Section: Covert Attention Alters Spatial Resolutionmentioning
confidence: 56%